METODE TRANSFER PENGETAHUAN PADA PERUSAHAAN KELUARGA DI INDONESIA - Gabriella Hanny Kusuma (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
This study aims to explore the intergenerational knowledge transfer mechanism in family frms. Using the case study method, this qualitative research examines 14 family frms. Data were obtained through semi-structured inter views with participants, and then analyzed by using content analysis. Visual mapping and temporal bracketing techniques were also used for data analysis. Data source triangulation and member checking methods were utilized to test the validity and reliability of the data. The fndings show that interpersonal relationship between the predecessor (parents) and the successor (children) is needed in the knowledge transfer process. The physical presence of the predecessor and the direct involvement of the successor in the business are two important elements in the knowledge transfer process, wherein the successor obtains information from inside and outside the frm. The intergenerational knowledge transfer process allows the successor to get real experiences and to run their own experiments. Learning-by-doing is a knowledge transfer method that is commonly used in family firms.Keywords: family business company, predecessor, successor, transfer knowledge.